2017
DOI: 10.1111/ejh.13001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and clinical determinants of time‐to‐positivity of blood cultures in patients with neutropenia

Abstract: The expected TTP offers guidance in the management of patients with neutropenia and suspected bacteraemia. The knowledge of negative BC can support a change in working diagnosis, and impact clinical decisions as soon as 24 hours after BC collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Our study showed a median TTP of 12 h with 92.1% episodes being positive within the first 24 h. These results are similar to the published work by Lambregts et al [15] reporting 190 episodes of BSI throughout a 4-year period for febrile neutropenic individuals with onco-haematological diseases in a tertiary care hospital with a stem cell transplant programme. Even though these authors measured TTP since collection of blood cultures, and our paper reports TTP from start of incubation, the main results are similar, with a median TTP of 15.6 h and 91.6% of episodes having a TTP <24 h. However, that paper reveals significant weaknesses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed a median TTP of 12 h with 92.1% episodes being positive within the first 24 h. These results are similar to the published work by Lambregts et al [15] reporting 190 episodes of BSI throughout a 4-year period for febrile neutropenic individuals with onco-haematological diseases in a tertiary care hospital with a stem cell transplant programme. Even though these authors measured TTP since collection of blood cultures, and our paper reports TTP from start of incubation, the main results are similar, with a median TTP of 15.6 h and 91.6% of episodes having a TTP <24 h. However, that paper reveals significant weaknesses.…”
Section: Discussionsupporting
confidence: 91%
“…However, progressive advances and continued monitoring in microbiological laboratories have shortened the time-to-positivity (TTP) of blood cultures significantly. Current information exploring the TTP of blood cultures from individuals with onco-haematological diseases with febrile neutropenia is scarce [15]. Determining the probability of bacteraemia when blood cultures have remained negative within the first 24 h would have a great impact on assisting the promptness of antibiotic stewardship de-escalation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Even with important differences between the two institutions, Cobos-Trigueros et al could define a two-step algorithm to predict C. glabrata bloodstream infection, reaching performance measures of 79% (sensitivity), 90% (specificity), 59% (positive predictive value) and 96% (negative predictive value) [6]. In Puerta-Alcade et al's work, the frequency of positive bottles within 24 h (92.1%, [2]) and TTP variation according to pathogen groups were confirmed elsewhere [3], including paediatric patients with sepsis [6]. Several studies focused on specific patient groups (e.g.…”
mentioning
confidence: 95%
“…Concerning the potential usefulness of TTP to guide antimicrobial therapy, most works have addressed onco-haematological patients with febrile neutropenia [2,3], probably because these patients combine a high risk of antimicrobial selective pressure with a high risk of bloodstream infection. In this issue, Puerta-Alcade et al advocate, based on a retrospective study, early deescalation at 24 h [2] instead of 48e96 h as commonly advised because (i) the great majority of episodes with positive blood culture are positive within the first 24 h, (ii) positive episodes with TTP 24 h are commonly optimally treated infections, catheter-related infections, or infections caused by slowly growing microorganisms such as Candida or anaerobic Gram-negative bacteria, and (iii) growth of multidrug-resistant Gram-negative bacilli is exceptional beyond 24 h. With similar logistics, other studies show short TTP in agreement with Puerta-Alcade et al's results: median TTP, although it varied between bacterial groups, was 24 h except for yeasts (see ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation